Exciplex Formation in Lipid‐bound Escherichia coli Flavohemoglobin. Issue 11 (28th April 2021) - Marcelli, Agnese; Patrizi, Barbara; Bonamore, Alessandra; Boffi, Alberto; Becucci, Maurizio; Foggi, Paolo
Abstract: Flavohemoglobins have the particular capability of binding unsaturated and cyclopropanated fatty acids as free acids or phospholipids. Fatty acid binding to the ferric heme results in a weak but direct bonding interaction. Ferrous and ferric protein, in presence or absence of a bound lipid molecule, have been characterized by transient absorption spectroscopy. Measurements have been also carried out both on the ferrous deoxygenated and on the CO bound protein to investigate possible long‐range interaction between the lipid acyl chain moiety and the ferrous heme. After excitation of the deoxygenated derivatives the relaxation process reveals a slow dynamics (350 ps) in lipid‐bound protein but is not observed in the lipid‐free protein. The latter feature and the presence of an extra contribution in the absorption spectrum, indicates that the interaction of iron heme with the acyl chain moiety occurs only in the excited electronic state and not in the ground electronic state. Data analysis highlights the formation of a charge‐transfer complex in which the iron ion of the lipid‐bound protein in the expanded electronic excited state, possibly represented by a high spin Fe III intermediate, is able to bind to the sixth coordination ligand placed at a distance of at 3.5 Å from the iron. A very small nanosecond geminate rebinding is observed for CO adduct in lipid‐free but not in the lipid‐bound protein. The presence of the lipid thus appears to inhibit the mobility of CO in the heme pocket. Abstract : Exciplex in Lipid‐bound Flavohemoglobin : Transient absorption spectroscopy has been used to investigate the presence of a long‐range interaction between the acyl chain moiety of fatty acid and the ferrous heme in E. coli Flavohemoglobin. Data analysis of the lipid‐bound derivative reveal the formation of a charge‐transfer complex after heme excitation, i. e., an exciplex, in which the high spin Fe III intermediate, binds to the sixth coordination ligand placed at a distance of at 3.5 Å from heme iron.